Extensible and robust functional reactive programming - Perez Dominguez, Ivan (2018)
Programming GUI and multimedia in functional languages has been a long-term challenge, and no solution convinces the community at large. Purely functional GUI and multimedia toolkits enable abstract thinking, but have enormous maintenance costs.